Design and Fabrication of a Microfluidic Chip Device for Colorimetric Quantitative Analysis of Albumin in Urine Matrix Solutionn - Karmanto, Karmanto; Fikroh, Retno Aliyatul; Muna, Laili Nailul (Molekul, 2025)
ABSTRACT. The existence of albumin in urine indicates kidney impairment, referred to as albuminuria. Early detection of kidney dysfunction can be done through the examination of urine albumin levels. This research aims to develop a microfluidic chip device for quantitative analysis of albumin in urine matrix solution using colorimetry with a smartphone-based device. The microfluidic chip device for albumin is tested and evaluated through functional tests and analysis of the quality of measurement data generated. The functional tests of the colorimetric system include testing the hydrophobic properties of the fluid on the material surface, fluid distribution pattern, color appearance, and leakage. The quality of measurement data is evaluated based on the predictive ability of the partial least squares regression models generated by data measurement for predicting the albumin levels accurately and precisely. A prototype of the microfluidic chip device for albumin was made from transparent acrylic material, with a 3-dimensional vertical fluid flow design consisting of two main parts: the inlet section and the colorimetric system for visual fluid observation. Based on the functional tests, it is found that the acrylic material in the colorimetric system has a hydrophilic surface characteristic with a contact angle of 61.15o. The fluid can flow and distribute well within the colorimetric system without producing bubbles. The color appearance in the colorimetric system is also visualized well without fluid leakage. On the other hand, RGB HSL data, as the digital image identity of the training and test samples, can be used as predictor variables. The method validation demonstrated acceptable sensitivity, with an LOD of 3.368 mg/dL and an LOQ of 11.825 mg/dL. Precision at 16 mg/dL showed good repeatability (RSD 0.561%, recovery 99.26%;) and reproducibility (RSD 2.147%, recovery 101.42%). These results confirm the method's reliability for albumin quantification at the tested concentration level. Keywords: Albumin, albuminuria, colorimetry, microfluidic chip, PLSR, urine analysis